DINAMIKA PEROLEHAN SUARA PARTAI GOLKAR KOTA PEKANBARU DALAM PEMILIHAN UMUM TAHUN 2024 - Utama, Rezaldi Prastya; Handoko, Tito (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The Golongan Karya Party (Golkar) is the oldest and largest political organization in Indonesia, with an extensive network of cadre development spread across all regions of the country. The issue in this study isthat Golkar Party experienced only a slight increase in votes and seats in the 2024 Pekanbaru City Regional Legislative Election, gaining only 8.116 more votes (from 46.252 votes in 2019 to 54.368 votes in 2024) and ones additional seat (from 4 seats in 2019 to 5 seats in 2024). This raises concerns and presents a challenge for Golkar, being a large party with many members and a strong supporter base. The purpose of this research is to describe the dynamics of Golkar Party’s vote acquisition in the 2024 Pekanbaru City Regional Legislative Election and to identify the factors influencing these dynamics. This research applies the theory of party institutionalization proposed by Basedau and Stroh (2008), which includes Roots in Society, Autonomy, Level of Organization, and Coherence. The study employs a descriptive qulitatve research method, with primary and secondary data as the main sources. Data collection techniques include interviews and documentation. The data analysis techniques used are Data Reduction, Dta Presentation, and Conlusion Drawing. The research results show that Golkar Party has made efforts to implement the indicators of party institutionalization. However, these efforts werw not fully optimilized, leading to fluctuations in Golkar Party’s vote acquisition in the 2024 Pekanbaru City Regional Legislative Election. The influencing factors include both internal and external factors. Internal factors involve Golkar Party’s internal performance during the election process, form the selection of legislative candidates to campaigning. External factors include the Sainte-Lague Divisor system and shifts in the number of voters who remain pragmatic. Keywords: Golkar Party, Vote Acquisition, Party Intitutionalization, Internal Factors, and External Factors.